Enhancing student nurses’ ethical skills via simulation-based learning: barriers and opportunities - Richard M. Rasesemola; Manoko P. T. Molabe (BMC Nursing, 2025)
Abstract Background Nurses lack skills to analyse ethical problems, and some feel powerless and frustrated when encountering and having to deal with ethical dilemmas in clinical practice. The lack of ethical competence among nurses might somewhat be related to the neglect and side-lining of ethics in the education system. For those nurse educators who are facilitating ethics within their curriculum, their strategies and practices are inefficient due to lack of resources. Lack of efficient strategies to facilitate ethical competence create threats to ethical values in healthcare with a potential to jeopardise patients’ health outcomes. Methods This was a qualitative, descriptive, exploratory, and contextual research that was done in one higher education institution among 9 nurse educators and clinical nurse preceptors. Online semi-structured interviews were conducted, data were transcribed and analysed following Giorgi’s thematic analysis method. Results Two themes with 5 related subthemes emerged from the data. The theme of barriers that hinder the facilitation of ethical skills for nursing students indicated how Covid-19 pandemic lead to constraints that lead to facilitators focusing on clinical skills and procedures and side lining ethics education. While the theme transformative approaches to fostering ethical competency through simulation– based learning indicated some strategies that facilitators could adopt to ensure efficient ethics education for nursing students. Conclusion Barriers related to insufficient human resources and infrastructure made it almost impossible to facilitate ethics education among nursing students, especially during Covid-19 pandemic. This research offers some transformative solutions that could be adopted by higher education institutions to ensure that ethical competence is effectively facilitated.